Metal-wood crane beam calculation - A. K. Yusupov; H. M. Muselemov; T. O. Ustarhanov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The development of structures and calculation of metal-wood crane beams are associated with specific difficulties. The article discusses the methods of calculation and design of metal-wood crane beams. In this case, an algorithm is described that allows designing systems that are rational in terms of material consumption. Methods. As an example, a metal-wood beam with a span of 12 m is used, which is supported by overhead cranes with a load capacity of 30 tf. The operation of a metal-wood crane beam was compared with a glue laminate crane beam without reinforcement. The reinforcement elements are "discarded" and replaced with elasto-yielding supports to calculate a glue laminate beam reinforced with metal elements (or a metal-wood beam). The flexibility of these supports is taken into account using the elastic support ratio r, which is determined depending on the stiffness of the supports, and the force in the metal elements is derived from the nodes balance. Result. In both variants of loading metal-wood crane beams, it was shown that the greatest bending moment occurred when the bridge wheel was located above the elastic support. Conclusion. It is rational to use a metal-wood crane beam when operating bridge cranes with a lifting capacity of up to 30 tf; metal-wood crane beams are recommended to be designed with spans up to 12 m; the comparison of glue laminate crane beams with metal-wood beams showed that metal-wood beams were 40-55% more efficient.